Herllo, thatsmessedup!
You are right!
They say the answers for 25 and 28 are both 0. . They are wrong!.
$\displaystyle 25.\;\frac{x}{x-1} - \frac{x}{1-x}$
$\displaystyle \frac{x}{x-1} - \frac{x}{1-x} \;=\;\frac{x}{x-1} - \frac{x}{\text{-}(x-1)} \;=\;\frac{x}{x-1} + \frac{x}{x-1} \;=\;\frac{2x}{x-1}$
$\displaystyle 28.\;\frac{1}{(x-1)(x-2)} + \frac{1}{(x-2)(x-3)}$
$\displaystyle \frac{1}{(x-1)(x-2)}\cdot\frac{x-3}{x-3} + \frac{1}{(x-2)(x-3)}\cdot\frac{x-1}{x-1}$
. . . $\displaystyle =\;\frac{x-3}{(x-1)(x-2)(x-3)} + \frac{x-1}{(x-1)(x-2)(x-3)} $
. . . $\displaystyle =\;\frac{(x-3) + (x-1)}{(x-1)(x-2)(x-3)}$
. . . $\displaystyle =\;\frac{2x-4}{(x-1)(x-2)(x-3)} $
. . . $\displaystyle =\;\frac{2(x-2)}{(x-1)(x-2)(x-3)} $
. . . $\displaystyle =\;\frac{2}{(x-1)(x-3)}$
I'm actually get this practice exam from here Glendale Community College : Sample Tests and Study Packets which is ridiculous!